Integrating green finance into vocational education: Curriculum design and implementation strategies for sustainable development - Lyu, Jia-Ying; Lin, Wen-Bao; Wang, Ping-Shen (American Journal of STEM Education, 2025)
Drawing on literature review, document analysis, and 18 semi-structured stakeholder interviews carried out at eight Taiwanese technological universities (January–March 2025), this study proposes a three-dimensional curriculum framework theoretical foundation, practical applications, and project-based learning for embedding green-finance competencies in vocational education. The qualitative evidence highlights four implementation strategies: faculty development, modular course design, deep industry partnerships, and authentic assessment. Findings underscore that aligning curricula with industry demand and sustainability mandates can bridge the current green skills gap in vocational education and enhance graduate employability in sustainable finance roles.